The Relationship between Anxiety and Compliance in Conducting Antenatal Care during the Covid 19 Pandemic for Pregnant Women at the Sekolaq Darat Health Center in 2022 - Listeri; Edi Sukamto; Siti Raihanah (Formosa Journal of Science and Technology, 2023)
This study aims to determine the relationship between anxiety and adherence of pregnant women to antenatal care during the COVID-19 pandemic. This type of research is descriptive correlative with cross sectional design. The population in this study were all trimester I-III pregnant women at the Sekolaq Darat Health Center in 2022 as many as 41 people. The sampling technique uses total sampling so that the entire population is sampled in this study. Data was collected using observation sheets, questionnaires, MCH books, and the DASS (Depression Anxiety Stress) instrument to measure anxiety. Data were analyzed using the chi square test. The results of the hypothesis test obtained a p-value = 0.00 (p <0.05). So it can be concluded that there is a relationship between anxiety and compliance with antenatal care during the COVID-19 pandemic for pregnant women at the Sekolaq Darat Health Center in 2022.